Ecological and physiological basis for the distribution of woody plants along water availability gradients in the Southeastern United States mixed forest - Abit, Pamela Po (ProQuest Dissertations & Theses Global, 2008)
"Higher temperatures under climate change are likely to result in greater evaporation and increased soil moisture deficits. Increased drought will likely cause a shift in the vegetation distribution. This study focused on woody plants of the Southeastern United States mixed forest. Although water is not a primary limiting factor in this forest, species distribution suggests that water availability exerts a strong control on the success of woody plants. I used a comparative approach to understand environmental factors and corresponding species traits that determine species composition across a gradient of water availability. I compared hydraulic architecture, vulnerability to cavitation, and the ability of xeric and mesic species to germinate, grow and survive under varying levels of water stress. Congeneric pairs composed of one xeric and one mesic species were used. Seeds were subjected to polyethylene glycol solutions of different water potentials to compare the effects of water availability on germination of xeric and mesic species. I used understory saplings to compare the difference in the xylem hydraulic properties between xeric and mesic species and the air-injection method was used to determine differences in their xylem vulnerability to cavitation. I performed a dry-down experiment to compare the ability of the xeric and mesic species to survive extreme drought by evaluating survival after re-watering subsequent to drought exposure. Growth performance was evaluated by measuring electron transport rate (ETR), stomatal conductance (gs), shoot and root biomass of seedlings that were exposed to different levels of water (well-watered, dry, and flooded) and nutrients (high and low). Results indicate that the ability to germinate under drought did not differ consistently between xeric and mesic species, but, germination ability under drought was associated with the ability to maintain turgor. Stems of xeric species were less vulnerable to wilting than mesic species under drought stress. I found greater resistance to xylem cavitation in xeric species than mesic species. It appears that cavitation resistance was independent of specific conductivity and wood density since I did not find any trade-off between specific conductivity and vulnerability to cavitation among the woody plants examined. In the growth performance study, xeric species tend to have lower whole plant biomass, higher Root:Shoot (R/S) ratio, higher coarse root mass ratio (CRMR) and less reduction in gs under drought stress than mesic species. The higher stomatal conductance and lower photorespiration rates among the mesic species may have influenced their increased photosynthetic rates, thereby producing a greater total plant biomass than xeric species. Species distribution along water availability gradients appears to be better explained by the ability of seedlings to resist cavitation, to tolerate and survive water stress, and by their biomass allocation patterns, rather than by their ability to germinate under drought."--Abstract.